Darunavir does not prevent SARS-CoV-2 infection in HIV patients. (July 2020) - Riva, Agostino; Conti, Federico; Bernacchia, Dario; Pezzati, Laura; Sollima, Salvatore; Merli, Stefania; Siano, Matteo; Lupo, Angelica; Rusconi, Stefano; Cattaneo, Dario; Gervasoni, Cristina
Graphical abstract: